Current-reported outcome domains in studies of adults with a focus on the treatment of tinnitus: protocol for a systematic review. - Hall, DA (2015)
INTRODUCTION: In Europe alone, over 70 million people experience tinnitus. Despite its considerable socioeconomic relevance, progress in developing successful treatments has been limited. Clinical effectiveness is judged according to change in primary outcome measures, but because tinnitus is a subjective condition, the definition of outcomes is challenging and it remains unclear which distinct aspects of tinnitus (ie, 'domains') are most relevant for assessment. The development of a minimum outcome reporting standard would go a long way towards addressing these problems. In 2006, a consensus meeting recommended using 1 of 4 questionnaires for tinnitus severity as an outcome in clinical trials, in part because of availability in different language translations. Our initiative takes an approach motivated by clinimetrics, first by determining what to measure before seeking to determine how to measure it. Agreeing on the domains that contribute to tinnitus severity (ie, 'what') is the first step towards achieving a minimum outcome reporting standard for tinnitus that has been reached via a methodologically rigorous and transparent process. METHODS AND ANALYSIS: Deciding what should be the core set of outcomes requires a great deal of discussion and so lends itself well to international effort. This protocol lays out the first-step methodology in defining a Core Domain Set for clinical trials of tinnitus by establishing existing knowledge and practice with respect to which outcome domains have been measured and which instruments used in recent registered and published clinical trials. ETHICS AND DISSEMINATION: No ethical issues are foreseen. Findings will be reported at national and international ear, nose and throat (ENT) and audiology conferences and in a peer-reviewed journal, using PRISMA (Preferred Reporting Items for Systematic reviews and Meta-analysis) guidelines. TRIAL REGISTRATION NUMBER: The systematic review protocol is registered on PROSPERO (International Prospective Register of Systematic Reviews): CRD42015017525.